Effect of functional strength training on snatch performance for weightlifters - Salaheldeen Gharib (Turkish Journal of Kinesiology, 2018)
This study aims to improve the functional strength (Strength - Power- Balance) using the Functional strength Exercises and knowledge and their impact on Snatch performance for lifters. Applied study on a sample of (12) weightlifters Registered Egyptian Federation of weightlifting/ Egypt of season 2016/2017, the researcher used an experimental method to design two groups, one Functional strength group consisted of (6) lifter and the other control group of (6) lifter. Where the mean age of (20.17 ± 3.97 years) and height (166.00 ± 3.29 cm), weight (79.08 ± 14.02 kg) and age training (8.83 ± 4.02 years) for the Functional strength group, while the Mean age (18.83 ± 2.14 years), height (165.83 ± 8.59 cm), weight (69.07 ± 5.91 kg) and age training (6.33 ± 3.14 years) for the control group Methods. The Functional strength group underwent a functional strength Exercises while the control group underwent Traditional exercises. Functional strength Exercises Continued for 12 Weeks 3 times per week and the training session lasted 90-120 a minute.  The pre and post for the two control and Functional strength group a measured functional strength (Strength - Power- Balance) and snatch performance tests for the two groups. Statistical analysis of the experimental and control data SPSS was used to apply formulas statistical by calculating: Mean, Standard deviation, Mann-Whitney and Wilcoxon test. Results. The results showed the use of a functional strength Exercises resulted in an improvement statistically significant at a level of functional strength training and snatch performance for weightlifters. This study confirms that a functional strength (strength - Power- Balance) training improves snatch performance for lifters. Conclusions. The Weightlifting Federation and attention by coaches trained in the application of a functional strength training weightlifters programs given the positive impact on the lifters.